Palladium(II) complexes with R(2)edda-derived ligands. Part V. Reaction of O,O '-diethyl-(S,S)-ethylenediamine-N,N '-di-2-(3-methyl)butanoate with K-2[PdCl4] - Radic, Gordana P.; Glodovic, Verica V.; Kaluderovic, Goran N.; Heinemann, Frank Wilhelm; Trifunovic, Srecko R. (Transition Metal Chemistry, 2011)
The reaction of K-2[PdCl4] with [(S,S)-H-2(Et)(2)eddv]Cl-2 diester (O,O'-diethyl-(S,S)-ethylenediamine-N,N'-di(2)-(3-methyl)butanoate) (1) resulted in [PdCl2(S, S)-(Et) eddv-kappa N-2,N', kappa O] (2) complex with one hydrolyzed ester group. The compound was characterized by spectroscopic methods and it was found that the reaction is diastereoselective (H-1 and C-13 NMR; one diastereoisomer of four possible). In addition, the structure of 2 was confirmed by X-ray diffraction analysis, indicating that the product is the (R,R)-N,N'-configured isomer. DFT calculations support the formation of one diastereoisomer of 2.